Calculation of the Friction Coefficients of Flax Stems according to their Roughness Characteristics - V. G. Chernikov; R. A. Rostovtsev; R. A. Popov; V. Yu. Romanenko; A. A. Rostovtsev (Сельскохозяйственные машины и технологии)
When harvesting flax, its stems get into contact with the working elements of flax harvesting machines. The authors have found that the diversity of materials used to manufacture the working elements made it necessary to calculate the friction coefficients in the interaction between the stems and these materials, since it is not always possible to do this experimentally. They confirmed the possibility of calculating the friction coefficients in the butt, middle and apical parts of the stem. Research purpose Calculation of the friction coefficients of flax stems according to the given microgeometry characteristics of their surface.Materials and methods The studies were carried out on a standard device, a profile meter-and-recorder made by the Kalibr plant, make 201. Common (fibre) flax of the Mogilevskiy 2 variety at the stage of brown ripeness, at a humidity - 43.79 percent, with total length of stems – 78, 9 cm and a flax straw yield of 3.575 tons per hectare were chosen for the experiments. The flax crop was harvested by hand on the experimental field during the harvesting period. During the preparation of experimental samples, the flax stem was divided into three parts - butt, middle and apical. Each of the stem parts was divided into two halves along the axis, then one of the halves was unrolled and pasted on a solid base (steel plate). Profile diagrams of flax stems parts of were processed with conventional methods.Results and discussion The authors have obtained the friction coefficients of the stems of different humidity as they moved along the steel surface. It has been established that the calculated values of the friction coefficients are slightly higher than those obtained as a result of experiments. (Conclusions) It has been established that as the humidity of flax stems increases, the molecular component of the friction coefficient increases too. It has been determined that when the moisture content of the stems is 20-45 percent, the friction coefficient values range from 0.38 to 0.98 percent.